2013
DOI: 10.1111/eje.12017
|View full text |Cite
|
Sign up to set email alerts
|

Soft skills and dental education

Abstract: Soft skills and hard skills are essential in the practice of dentistry. While hard skills deal with technical proficiency, soft skills relate to a personal values and interpersonal skills that determine a person's ability to fit in a particular situation. These skills contribute to the success of organisations that deal face-to-face with clients. Effective soft skills benefit the dental practice. However, the teaching of soft skills remains a challenge to dental schools. This paper discusses the different soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 67 publications
2
59
0
9
Order By: Relevance
“…To aid discussion during the workshop, a reading list of relevant references was distributed to all registered participants. The references were categorised under the following subject headings: Selection of appropriate assessment tools; Selection of appropriate standard setting methods; Workplace‐based assessment; How best to assess “soft‐skills” such as professionalism, leadership and management …”
Section: Pre‐workhop Online Registrant Survey Results and Reading Listmentioning
confidence: 99%
“…To aid discussion during the workshop, a reading list of relevant references was distributed to all registered participants. The references were categorised under the following subject headings: Selection of appropriate assessment tools; Selection of appropriate standard setting methods; Workplace‐based assessment; How best to assess “soft‐skills” such as professionalism, leadership and management …”
Section: Pre‐workhop Online Registrant Survey Results and Reading Listmentioning
confidence: 99%
“…In addition, little attention has been paid to study differences across disciplines outside medicine. While much research has focused on the multifaceted and complex phenomenon of role modelling in diverse medical settings, limited evidence exists on the perceptions of dental 18 , 19 and pharmacy students 20 - 23 about role modelling. Therefore, we examined the insights as well as demographic attributes of graduating students across health disciplines (medicine, dentistry, and pharmacy)  to determine which professional and humanistic attributes demonstrated by medical teachers, as well as other potential factors, caused them to be perceived by students as PRMs and NRMs.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to convey messages clearly to patients, listen, be observant and respond to patients' needs, empathise, understand and carry out consultations in an organised and a professional manner are considered basic requirements of a competent dentist. [1] The clinical teachers agreed that a communication skills module should be included in the future dental curriculum. They suggested that such a course be embedded throughout the curriculum; the objective of this strategy would be to align what is taught and assessed.…”
Section: Discussionmentioning
confidence: 99%